Are internet prices sticky? - Patrick Lünnemann; Ladislav Wintr (European Central Bank (ECB), 2006)
This paper studies the behaviour of Internet prices. It compares price rigidities on the Internet and in traditional brick-and-mortar stores and provides a cross-country perspective. The data set covers a broad range of items typically sold over the Internet. It includes more than 5 million daily price quotes downloaded from price comparison web sites in France, Germany, Italy, the UK and the US. The following results emerge from our analysis. First, and contrary to the recent findings for common CPI data, Internet prices in the EU countries do not change less often than online prices in the US. Second, prices on the Internet are not necessarily more flexible than prices in traditional brick-and-mortar stores. Third, there is substantial heterogeneity in the frequency of price change across shop types and product categories. Fourth, the average price change on the Internet is relatively large, but smaller than the respective values reported for CPI data. Finally, panel logit estimates suggest that the likelihood of observing a price change is a function of both state- and time-dependent factors.
Keywords: E31; L11; 330; Internet; price setting behaviour; Price stickiness; Internet; Online-Handel; Preisrigidität; Deutschland; Frankreich; Großbritannien; Italien; USA